Alternate arm converter with thyristor-based director switches - Soto Sanchez, Diego Enrique; Martinez-Gomez, Manuel; Andrade Aguero, Ivan Eric; Pena, Ruben (My University, 2018)
The Modular Multilevel Converter (MMC) is the choice topology for integration of renewable energy power plants into the grid, through submarine HVDC cables and HVDC lines. Notwithstanding, the MMC requires significant large DC storage capacitors to mitigate for the large power pulsations that result from the single-phase AC to DC conversion process in their arms. The Alternate Arm Converter (AAC), which combines MMC arms with conventional valves (Director Switch), has the potential to cut the number of modules to half of that of the conventional MMC. Further, it is capable of blocking DC faults, an appealing feature for future DC networks. However, the AAC incurs higher power losses than conventional MMC. This work proposes the use of thyristors, instead of IGBTs, to implement the DSs of the AAC. This reduces conduction losses in DSs by approximately a half and makes the AAC more comparable to the conventional MMC, in terms of power losses, but with the advantage of reduced DC energy storage requirements. The principle of operation of the AAC, considering thyristor based DSs, is revisited here and a suitable control strategy to demonstrate its basic operation is developed. Proposals are verified through simulation studies using a switching converter model. Results confirm feasibility of proposed thyristor based DS and good performance of the proposed AAC.
Keywords: alternate arm converter; hvdc; modular multilevel converter